Absorbsi Prinsip ”Rebus Sic Stantibus” Dalam Kerangka Pembaharuan Hukum Perjanjian Nasional - Dwi Primilono Adi (Jatiswara, 2015)
Rebus Sic Stantibus principle is an unpopular principle in civil law system because this principle is taken by Common Law principle. In theory, contractual implementation, in the essence, submit to pacta sunt servanda principle. Pacta sunt servanda principle, in the contemporary, has a challenge from they who argue the principle prevail only when there is no radically change condition in the contract. Rebus Sic Stantibus doctrine or it is well known with clausula Rebus Sic Stantibus is a radically change condition because extrime trouble for each other party to fulfill the contract and imposibble the contract to be implemented. Thus, it must be renegotiate to requirement in the contract. The purpose of this research is to know what the change condition charateristic (rebus sic stantibus) in the implementation of contract as a diffrentiation with state of emergency (force majeure). Research method is juridical normative where a legal reserach procedure to discover truth base on logical law from nomative side. The result of this research that the change condition charateristic (Rebus Sic Stantibus) in the implementation of contract as a diffrentiation with state of emergency (Force Majeure) is in the implementation of contract imposibble to do it because of the legal reason, avoid economic trouble or economic imposibility, whereas in Rebus Sic Stantibus, the reason why the contract is not implemented because the contractual implementation is too difficult to do it, so include economic imposibility. Therefore, difficult level of Rebus Sic Stantibus is under Force Majeure.